NEEDS FOR TEACHERS' PARTICIPATION IN INTERNAL EDUCATION QUALITY ASSURANCE OF BASIC EDUCATION SCHOOLS UNDER KHONKAEN PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Janpeng, Vipavee; Piampuechana, Niyada (Journal of Buddhist Education and Research (JBER), 2022)
The purposes of this research were to study the needs for participation of teachers in the implementation of internal education quality assurance in schools and to study recommendations for participation of teachers in the implementation of internal education quality assurance in schools under KhonKaen Primary Educational Service Area Office 2. The sample group used in this research consisted of administrators and teachers under KhonKaen Primary Educational Service Area Office 2, with the total number of 315 people. The sample size was determined by Taro Yamane formula (1973) using stratified random sampling. The tool used for data collection was 5-level rating scale questionnaire with content validity (IOC) of 0.67– 1.00 and reliability of the whole questionnaire at 0.84. The statistics used to analyze data comprised percentage, frequency, mean, standard deviation and PNI modified index. The research results were found that The current situation of teachers' participation in the implementation of internal education quality assurance in basic education schools under KhonKaen Primary Educational Service Area Office 2, in overall, was found that the practice was at a moderate level, the desirable conditions for teachers' participation in the implementation of internal education quality assurance in basic education schools under KhonKaen Primary Educational Service Area Office 2, in overall, was at the highest level and the analysis results of the needs for teachers' participation in the implementation of internal education quality assurance in basic education schools under KhonKaen Primary Educational Service Area Office 2were found that the aspect with the most need was assessment and audit of internal education quality and the implementation of self-assessment reports, followed by the development of educational quality, monitoring and implementation, the implementation of educational development plan, educational development planning, the least important aspect was educational standard setting of the schools. Recommendations for teachers' participation in the implementation of internal education quality assurance in basic education schools under KhonKaen Primary Educational Service Area Office 2 consisted of the important aspects as follows: 1) On aspect of educational standard setting, the administrators and teachers should participate in decision-making to determine the value of achievement goals of each standard and indicators. 2) On educational development plan, the administrators and teachers should participate in the implementation of work plan of schools in accordance with internal education quality assurance within educational institutions. 3) On the implementation of educational development plan, the administrators and teachers should participate in decision-making educational development planning of schools in accordance with the standard and indicators of quality assurance. 4)assessment and audit of internal education quality, the administrators and teachers should participate in assessment to report the self-assessment results to school administrators. 5) On monitoring and implementation, the administrators and teachers should continuously participate in assessment for supervising, monitoring and auditing various projects. 6) On the implementation of self-assessment reports, the administrators and teachers should participate in the preparation of self-assessment report in accordance with quality standard. 7) On the development of educational quality, the administrators and teachers should participate in the operation to develop the schools into a professional learning community where all teachers and personnel in schools must be learning personnel.